Cultivating Digital Learning Culture: Perspectives of Pre-Service English Teachers at a Private Islamic University in Yogyakarta - Suryanto, Suryanto; Panuntun, Tyas (Journal of Foreign Language Teaching and Learning, 2000)
Background: The transformation of education in the 21st century demands the development of a digital learning culture that goes beyond merely providing access to technology. It also requires the integration of academic ethics, collaborative practices, and digital literacy into the teaching and learning process. In response to these demands, this study is needed to explore the practices and challenges of fostering a contextual and sustainable digital learning culture among prospective English teachers. Objective: This paper investigates the practices and challenges in the development of a digital learning culture among pre-service English teachers at a private Islamic university in Yogyakarta. Methods: Utilizing a descriptive qualitative design, the research captures the perceptions and experiences of six participants from the 2021 cohort, selected through purposive sampling. Data were gathered via online interviews conducted in Indonesian to ensure clarity and comfort, followed by rigorous analysis involving transcription, member checking, and systematic coding (open, analytical, axial, and selective). Findings: Findings reveal six key practices for fostering a digital learning culture: adherence to academic ethics, staying updated with digital tools, promoting digital literacy, employing student-centered learning, participating in training programs, and fostering collaboration. Three significant challenges were identified: managing digital learning activities, fears of digitization replacing teachers, and negative perceptions of digital learning’s value. Conclusion: The study concludes that addressing these challenges through targeted training, ethical practices, and institutional support is essential for effectively implementing a digital learning culture in English education.